Case report: Complete paternal isodisomy on chromosome 18 induces methylation changes in PARD6G-AS1 promotor in a case with arthrogryposis - Moch, Johanna; Radtke, Maximilian; Gburek-Augustat, Janina; Karnstedt, Maike; Schönnagel, Senta; Drukewitz, Stephan H.; Pilgram, Laura; Hentschel, Julia; Schumann, Isabell (Frontiers in Genetics, 2023)
Uniparental disomy (UPD) is the inheritance of both alleles of a chromosome from only one parent. So far, the detection of UPDs in sequencing data is not well established and a known gap in nextgeneration sequencing (NGS) diagnostics. By developing a new tool for UPD detection, we reevaluated an eight-year-old individual presenting with scoliosis, muscle weakness and global developmental delay. Previous panel analysis identified a homozygous likely pathogenic loss-offunction variant in the PIEZO2-gene associated with arthrogryposis (OMIM # 617146). Interestingly, during a re-evaluation process, we identified a region of homozygosity (ROH) covering over 95% of chromosome 18. Segregation and microsatellite analysis within the family revealed that only the father is a heterozygous carrier of the variant in PIEZO2 and confirmed paternal uniparental isodisomy (iUPD) on chromosome 18 in the individual. Further methylation analysis indicated demethylation of the promotor region of PARD6G-AS1, which is described to be maternally imprinted and could possibly influence the individuals' phenotype. Our report describes the first complete iUPD on chromosome 18 and highlights that UPDs can be a cause for homozygous pathogenic variants, which reduces the risk of reoccurrence in case of a new pregnancy in comparison to an autosomal recessive inheritance trait significantly.